Evaluasi Usability pada Aplikasi Grab dengan Menggunakan Metode Pengujian Usability - Nabilla Ridha Permana; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Grab is application of transport provider that offers several services. The service is transport service, courier service, and food service. Grab application has grown rapidly by seeing the application has been downloaded more than 10 million times. However, users from Grab application feel that application still has flaws, including the accuracy of the map when determine the location is still lack and when users entered the destination location is not detected by the application. From some user feedback, Grab application still have problems. Therefore, Grab application need problems digging and measurement of usability level. Usability testing method was used to problems digging in Grab application and to measure usability level of Grab application by using the task scenario and a questionnaire. Testing were conducted to five respondents from new user of Grab application and the questionnaire were filled by 100 respondents from active user of Grab application. The evaluation result show the problems and usability levels Grab application. The problems of Grab application is the participant feel difficulty to make a payment, participant feel difficulty to search the home address or location of participant on the â€œpick-upâ€ column, and participant feel confused when the location doesn't match with map of application. The usability level results are 100% of level ease of the user, 0,013 of level speed of the user, 0,13 of user's error rate, and level of user satisfaction is 40%-50% of Grab application.